A Study on Benchmarking Parameters for Intelligent Systems - Misir, Rajesh; Mitra, Malay; Samanta, RK (International Journal of Computer Sciences and Engineering, 2015)
Intelligent automated decision support systems are now found to be very much useful in various fields. In bioinformatics and machine learning in general, there is a large variation in the predictive measures that are used to evaluate intelligent systems. If we do not assess the accuracy of model's prediction, a vital step in model development, its application will have little merit. This work critically discusses different approaches to assess predictive performance and various test statistics. Choice of assessing strategy or validation for a specific application helps in determining the suitability of the model and in comparing the performances of different modeling techniques. The purpose of this paper is to serve as an introduction to various important benchmarking parameters and as a guide for using them in research.